2017
DOI: 10.1007/s40090-017-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of environmentally adapted lubricant basestock from jatropha curcas specie seed oil

Abstract: Jatropha curcas seed oil was studied for the synthesis of trimethylolpropane based biolube basestock via chemical transesterification of Jatropha methyl ester with trimethylolpropane (TMP) using calcium hydroxide catalyst. Reactions temperatures ranged between 80 and 160°C and methyl esters to TMP mole ratios ranged between 3:1 and 7:1. Product analysis, ester groups and physio-chemical properties were obtained by gas chromatography, Fourier transform infrared spectroscopy and American Society for testing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
3
23
1
Order By: Relevance
“…Thus, the optimum molar ratio for this study was at stoichiometric molar ratio of 3:1. On account of the stoichiometric reaction, the production of biolubricant can be much better accomplished by experimenting with a higher molar ratio of reactants to enhance reaction completion [5]. However, in our study, increasing molar ratio of FAME to TMP above its stoichiometric molar ratio, decreased the conversion of reactant to biolubricant.…”
Section: The Effect Of Molar Ratio On the Transesterification Reactiomentioning
confidence: 70%
See 2 more Smart Citations
“…Thus, the optimum molar ratio for this study was at stoichiometric molar ratio of 3:1. On account of the stoichiometric reaction, the production of biolubricant can be much better accomplished by experimenting with a higher molar ratio of reactants to enhance reaction completion [5]. However, in our study, increasing molar ratio of FAME to TMP above its stoichiometric molar ratio, decreased the conversion of reactant to biolubricant.…”
Section: The Effect Of Molar Ratio On the Transesterification Reactiomentioning
confidence: 70%
“…Hence, the use of non-edible oil as feedstock for biolubricant may reduce the competition within the current agricultural resources [3]. There are few studies reported for biolubricant production from vegetable oil based such as palm oil, Jatropha curcas oil, rubber seed oil, Karanja oil, rapeseed oil, waste cooking oil and sesame oil [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative onset temperature of EWCO was found to be 355 °C (Figure ). Comparison of thermal stability obtained for the present work with that for the other epoxidized oil reveals that the EWCO possesses relatively higher oxidative stability as compared to epoxidized canola oil (320 °C) and jatropha oil trimethylolpropane esters (240 °C) …”
Section: Physicochemical Characterization Of Prepared Ewcomentioning
confidence: 79%
“…As such, alternative oil sources for chemical process industries, which are renewable, biodegradable, and eco‐friendly, are currently being researched. Significantly, vegetable oils obtained from seeds and nuts are often used as a suitable substitute to mineral oil obtained from petroleum, 2 hence there is a need for the development/modification of the vegetable oils, into industrial products such as biodiesel, 3 biolubricants, 4,5 transformer fluid, 2 and other vital fuels that could be used as replacement for conventional mineral base fuels/fluids.…”
Section: Introductionmentioning
confidence: 99%